Optimization of fucoxanthin extraction obtained from natural by-products from Undaria pinnatifida stem using supercritical CO2 extraction method - Yin, Shipeng; Niu, Liqiong; Shibata, Mario; Liu, Yuanfa; Hagiwara, Tomoaki (Frontiers in Nutrition, 2022)
In recent years, edible brown seaweed, Undaria pinnatifida, has presented beneficial effects, which may be correlated with this species containing major bioactive compounds, such as carotenoids, fatty acids, and phytosterols. Marine carotenoid fucoxanthin is abundantly present in edible Undaria pinnatifida and features strong bioactive activities. The stem of Undaria pinnatifida is very hard to gnaw off and cannot be swallowed; therefore, it is usually discarded as waste, making it an environmental issue. Hence, making full use of the waste stem of Undaria pinnatifida is an urgent motivation. The present study aims to explore the optimal preparation technology of fucoxanthin from Undaria pinnatifida stems by using supercritical carbon dioxide methods and provides approaches for the extraction and preparation of bioactive compounds from a waste seaweed part. With the comprehensive optimization conditions applied in this study, the experimental yield of fucoxanthin agreed closely with the predicted value by >99.3%. The potential of α-amylase and glucoamylase to inhibit bioactive compounds was evaluated. Results demonstrated that the inhibition activity (IC50 value) of α-amylase (0.1857 ± 0.0198 μg/mL) and glucoamylase (0.1577 ± 0.0186 μg/mL) varied with extraction conditions due to the different content of bioactive components in the extract, especially fucoxanthin (22.09 ± 0.69 mg/g extract). Therefore, this study confirmed supercritical fluid extraction technology to be a useful sample preparation method, which can effectively be used to prepare fucoxanthin from waste marine resources. This method can potentially be applied in functional food and related industries.